The Effect of Assistance for Pregnant Women on Attitudes and Behavior Changes in Stunting Prevention - Oktaviani, Oktaviani; Sulistyawati, Reny (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: East Kotawaringin and Pulang Pisau Regency have highest prevalence of stunting, respectively, in Central Kalimantan Province. One of the efforts made through the assistance to improve the knowledge and skills of pregnant women. The study was aimed at analyzing the effectiveness of assistance on behavior and attitudes among pregnant women in the Pulang Pisau Regency. It also aimed to analyze the behavior of pregnant women shifting upon stunting.Method: It is a quasi-experimental study (n = 60), with pre-posttest group comparison. There are two groups, namely conventional (n = 30) and assisted through pocket book (n = 30). Socio-economic data was collected to draw the characteristics of the study subjects through questionnaire. A 2x2 chi-square and paired t-test was run in SPSS v. 18 for Windows.Results: The characteristics of the study respondents did not show any significant differences in attitudes and behaviors of stunting prevention in the Pulang Pisau district. The average change in attitude score shows a significant difference in the assisted group with a pretest of 65.8 ± 7.8, increased during the post-test of 75.7 ± 2.7. It is also an increase in understanding (n = 21). We concluded that pocket-book treatment is more effective in improving the attitude of pregnant women towards preventing stunting.